Chronological Changes in Tip Cells during Sprouting Angiogenesis of Development of the Retinal Vasculature in Newborn Mice. (2nd November 2017) - Cho, Chang Sik; Lee, Sang-Mok; Lee, Byung Joo; Jo, Dong Hyun; Kim, Jin Hyoung; Kim, Jeong Hun; Yu, Young Suk
ABSTRACT: Purpose : To investigate a sequential chronological change in tip cells during the development of the retinal vasculature in newborn mice. Materials and Methods : Newborn C57BL/6 mice were used for this study. To elucidate the patterns in the developing retinal vasculature, histology, and immunohistochemistry—antiplatelet endothelial cell adhesion molecule-1, anticollagen type IV, isolectin IB4 —were performed on sections of mouse retina on postnatal days (P)-4, -8, and -12. Staining patterns of isolectin IB4 -stained arterial and venous tip cells were compared in retinal wholemounts, in which the numbers and characteristics of tip cells were compared between arteries and veins on P-4, -6, and -8. In addition, vascular densities and branching patterns were compared between arterial and venous vascular forefront areas. Results : Tip cells in the superficial vascular plexus were observed until P-8. The number of tip cells was highest on P-6, decreasing dramatically from P-6 to P-8 (P-4, 165.2 ± 10.1, n = 17; P-6, 183.8 ± 19.4, n = 15; P8, 21.4 ± 6.4, n = 15) ( p < 0.05, respectively, t -test). There was a greater number of tip cells in veins versus arteries on P-4 and P-6 (P-4, 91.0 ± 9.2 veins versus 74.2 ± 10.4 arteries; P-6, 104.0 ± 10.2 veins versus 79.8 ± 11.3 arteries) ( p < 0.05, respectively). Arterial tip cells had thinner and longer sprouts compared with venous tip cells (basal thickness: 15.7 ± 8.7 veins versus 9.9 ± 3.5 μm arteries) (length, 20.3 ± 9.1 veins versus 37.1 ± 13.2 μm arteries on P-4) ( p < 0.05, respectively). Vessel areas and densities of vascular branch points were significantly higher around veins compared to arteries (vessel areas: 58.9 ± 1.2% veins versus 40.8 ± 1.9% arteries; vascular branch points, 1371.9 ± 136.7/mm 2 veins versus 1046.7 ± 175.5/mm 2 arteries) ( p < 0.05, respectively). Conclusion : The number of tip cells increased to a greater extent in the superficial vascular plexus of veins versus arteries until P-6. Consequently, there are more vessel areas and vascular branch points near retinal veins versus arteries. Arterial tip cells are longer and thinner than the shorter and thicker venous tip cells.